Description of sign-term in different terminological proposals in Brazilian Sign Language (Libras). - Castro Júnior, Gláucio de; Tuxi, Patricia; Francisco, Gildete da S. Amorim Mendes; Prometi, Daniela (TradTerm, 2023)
In recent years, there has been an increase in linguistic research on sign languages, particularly the development of terminological works (glossaries, vocabularies, and bilingual lexicons) involving Brazilian Sign Language (Libras) in the fields of Natural Sciences, Biomedical Sciences, and Health. As these domains contribute to the education of Deaf individuals in learning related content, this study aims to survey terminological proposals in Libras, particularly those with records of sign-terms. To achieve this, 18 works from the database of the "Google Scholar Brazil" platform were described. The intention is to understand the methodology involved in recording sign-terms in bilingual Portuguese and Brazilian Sign Language glossaries, vocabularies, and lexicons.